Latest progress in low-intensity pulsed ultrasound for studying exosomes derived from stem/progenitor cells - He, Yi-fang; Wang, Xia-li; Deng, Shuang-ping; Wang, Yan-li; Huang, Qing-qing; Lin, Shu; Lyu, Guo-rong (Frontiers in Endocrinology, 2023)
Stem cells have self-renewal, replication, and multidirectional differentiation potential, while progenitor cells are undifferentiated, pluripotent or specialized stem cells. Stem/progenitor cells secrete various factors, such as cytokines, exosomes, non-coding RNAs, and proteins, and have a wide range of applications in regenerative medicine. However, therapies based on stem cells and their secreted exosomes present limitations, such as insufficient source materials, mature differentiation, and low transplantation success rates, and methods addressing these problems are urgently required. Ultrasound is gaining increasing attention as an emerging technology. Low-intensity pulsed ultrasound (LIPUS) has mechanical, thermal, and cavitation effects and produces vibrational stimuli that can lead to a series of biochemical changes in organs, tissues, and cells, such as the release of extracellular bodies, cytokines, and other signals. These changes can alter the cellular microenvironment and affect biological behaviors, such as cell differentiation and proliferation. Here, we discuss the effects of LIPUS on the biological functions of stem/progenitor cells, exosomes, and non-coding RNAs, alterations involved in related pathways, various emerging applications, and future perspectives. We review the roles and mechanisms of LIPUS in stem/progenitor cells and exosomes with the aim of providing a deeper understanding of LIPUS and promoting research and development in this field.